عبد الكريم الخطيب ومهمة دعم الثورة الجزائرية - مقلاتي عبد الله (My University, 2016)
الملخص In this article we are trying to profile the personality of Abdul Karim al-Khatib, and his effective role in supporting the Algerian revolution, based on authentic sources which have emerged recently in Morocco and France, including his personal memoirs, issued in 2011, and his memoirs fellow strugglersMoroccans, and a certificate of Ahmed son of Bella and Mohamed Boudiaf, as well as the documents High Commissariat of the Ancients resisters,Morocco, theMoroccan NationalMuseum. We have adopted a historical approach and descriptive in order to uncover some of the historical facts, especially with the ones attached to sensitive issues, such as the nature of his relationship with the National Liberation Front and with the Moroccan authorities, and his commitment as a minister in the Government ofMorocco and the pro-Algerian Liberation Front. We talked about the main axes of the subject, starting with the definition charismatic freedom fighter, then clarify his relationship with the Algerian revolution in its first phase, and finally to highlight aspects of the great support of the Algerian revolution, particularly in the areas of armament and logistic support, connecting relationship with the Moroccan authorities, and support for revolutionary activity in Spain and in the rear bases Morocco brother. We have reached after research and exploration on the registration of important conclusions. Among them was that the character of Dr. Abdul Karim al-Khatib represented eventful path of nationalachievements, and made a lot of her country the first Morocco, in his capacity as commander of the Army of the Moroccan Liberation and minister and politically, also provided a valuable service to his country, the second of Algeria in a crucial phase of its history, it has been emptied after the independence ofMorocco to support the Algerian revolution. We also concluded that Khatib stressed his commitment to the Maghreb with the support of the Algerian revolution, and earn for this option, King Mohammed V position, so as to provide various forms of support to the Algerian revolution in need base Morocco vital, such as money and weapons, and to facilitate the supply and concentration and training activity inMorocco. Khatib has shown advanced positions in solidarity with the Algerian revolution and suffered because of that marginalization and distortion, however, has confirmed its commitment to support the Algerian revolution.